2007
DOI: 10.1111/j.1365-277x.2007.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of exposure for healthy eating in childhood: a review

Abstract: Children's food preferences are strongly associated with their consumption patterns. Identifying the factors that influence preferences is therefore crucial to the development of effective interventions to improve children's diets. Perhaps the most important determinant of a child's liking for a particular food is the extent to which it is familiar. Put simply, children like what they know and they eat what they like. From the very earliest age, children's experiences with food influence both preferences and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
358
3
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 533 publications
(403 citation statements)
references
References 50 publications
(87 reference statements)
20
358
3
14
Order By: Relevance
“…Gardening can increase children's exposure to FV and to positive modelling of peers and adults. Repeated exposure to FV can have a positive impact on liking and intake (Anzman-Frasca, Savage, Marini, Fisher, & Birch, 2012;Cooke, 2007). Gardening can provide opportunities for FV tasting and for learning in an interactive manner how fruit and vegetables are grown and their benefits to health (Ozer, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Gardening can increase children's exposure to FV and to positive modelling of peers and adults. Repeated exposure to FV can have a positive impact on liking and intake (Anzman-Frasca, Savage, Marini, Fisher, & Birch, 2012;Cooke, 2007). Gardening can provide opportunities for FV tasting and for learning in an interactive manner how fruit and vegetables are grown and their benefits to health (Ozer, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…5,15,17,18 Healthy food preferences are developed by exposing infants to a wide variety of textures and healthy foods while also limiting exposure to sweet, salty, and fatty foods. [19][20][21][22] These protective maternal feeding practices are potentially modifiable targets for early obesity prevention interventions. We report on the long-term outcomes (at ages 3.5 and 5 years) of 1 of few randomized controlled trials (RCTs) to have evaluated obesity prevention interventions targeting complementary feeding practices.…”
Section: What This Study Addsmentioning
confidence: 99%
“…3 Research has shown that children who start trying new foods and have plentiful options to choose from at an early age appear to have healthier diets throughout childhood. 4 Exposure to new foods at an early age as well as positive reinforcement from a parental figure or valued opinion has shown to aid in children and adolescents to be more involved in healthy eating behaviors. 4 The implications of unhealthy eating habits cannot be overemphasized.…”
Section: Introductionmentioning
confidence: 99%
“…4 Exposure to new foods at an early age as well as positive reinforcement from a parental figure or valued opinion has shown to aid in children and adolescents to be more involved in healthy eating behaviors. 4 The implications of unhealthy eating habits cannot be overemphasized. It was noted that people with easy access to energy dense, inexpensive foods (unhealthy food choices) combined with less energy expenditure (physical activity) requirements in their daily life tended to show a higher rate of obesity.…”
Section: Introductionmentioning
confidence: 99%